The effects of a land-based warm-up and accompanying passive heat retention on core body temperature, hormones, and subsequent performance in elite surfers - Cook, Christian J.; Serpell, Benjamin G.; Hanna, Lauren J. (Frontiers in Sports and Active Living, 2024)
Surfing is a high participation sport, yet little sport science research exists surrounding competitive performance in surfing. Given surfing’s inclusion as an Olympic sport from the 2020 Tokyo Olympics onwards, examination of performance would seem useful. In numerous land-based sports, and in swimming, the importance of warm-up and muscle heat is well documented. However, surfing is a unique sport in that it is undertaken both above and below water. Therefore, the aim of this research was to explore the effectiveness of a warm-up on readiness to perform in surfing. We discuss this in the context thermal regulation, hormone profile change, and subsequent expression of ‘power’ on waves – a key criteria which surfers are scored for. Nineteen advanced level surfers (i.e., competitive at just below national level in Australia, n = 15 males, n = 4 females) with mean (± SD) age, height and weight 24.5 ± 11.6 years, 174.7 ± 9.1 cm, and 67.7 ± 10.2 kg respectively were recruited. We adopted a repeated measures pre- and post-design whereby participants engaged in several simulated surfing competitions in an artificial wave pool; once after an active warm-up combined with a passive heat retention strategy (i.e., wrapping themselves in survival blankets – treatment), and once after no warm-up (control). Saliva samples were collected pre- and post- active warm up, or equivalent time under control conditions, for measurement of testosterone and cortisol. Increases in these hormones have previously been associated with enhanced readiness to compete. Our results demonstrate a clear thermoregulatory benefit to the treatment; with participants core body temperature typically higher from end of warm-up to end of the surf session following treatment (p ≤0.03), and magnitude of increase in core body temperature once in the water greater following treatment (p =0.01). A small magnitude upward change to testosterone (p =0.01) and cortisol (p ≤0.001) following warm-up was also observed. Finally, warm-up was associated with improved wave performance compared to control, with a 20% increase in performance score typically observed (p ≤0.01). We argue that the improved thermal profile may have influenced power and, as such, surfing performance was enhanced.